Toward Accessible Faith & Flourishing: Reconsidering Greek Intellectualism in Western Christian Theology. (14th September 2022) - Dow, Keith
Abstract: From its inception, the Western theological tradition exhibits a fascination with and appropriation of ancient Greek philosophy. This conceptual intertwining of philosophy and theology, as exemplified by Augustine and Aquinas, privileges rationality in the "natural order" and in the pursuit of virtue and human flourishing. Despite generative insights at the intersection of disability and theology in other aspects, the "enfolding" tendencies of a conceptual framework inherited from Plato and Aristotle relegate people with intellectual disabilities to the margins of human flourishing. Contemporary theologians vary in the extent of their adoption of these norms and ideals related to the natural order and human rationality. The future of disability theology must engage a "pastoral deconstruction" that questions these deep privileging tenants of the Western intellectual tradition if it is to welcome the richly embodied theological contribution of people with intellectual disabilities.